edeniss2020 Telemetry Dataset (Version 1.0.0) - Rewicki, Ferdinand; Norman, Tom; Vrakking, Vincent (2024)
The EDEN ISS 2020 Telemetry Dataset (edeniss2020) is a time series dataset. It consists of equidistant sensor readings stemming from 97 sensors in the [EDEN ISS](https://eden-iss.net/) research greenhouse. EDEN ISS was a (almost) closed loop research greenhouse build under the lead of the German Aerospace Center to study Controlled Environment Agriculture (CEA) techniques and plant growth for future long-term space missions. EDEN ISS was deployed in Antarctica in 2018 next to the german Neumayer III polar station and has been in operation for four years. The data contained in the edeniss2020 dataset was recorded during the third mission year in 2020 between 2020/01/01 and 2020/12/30. Every sensor within the dataset is related to one of the following Subsystems